On the skein theory of surfaces and the Bonahon-Wong asymptotic conjecture - Yu, Xiaoming (Nanyang Technological University, 2023)
One of the most important developments in low-dimensional topology is the Bonahon-Wong-Yang intertwiners [BWY21][BWY22], which are used to study the representa- tion theory of skein algebra and to explore a version of the volume conjecture. In this paper, we first discuss some topological properties of the four-punctured sphere such as its mapping class groups, triangulations and shear parameters; and then we investigate the Bonahon-Wong- Yang intertwiners of four-punctured sphere and try to make relevant calculations of certain pseudo-Anosov maps.